Psychometric properties of a food buying styles scale (Eec-ali) in university students Propiedades psicométricas de una escala de estilos de compra de alimentos (Eec-ali) en estudiantes universitarios - Denegri, Marianela; García, Constanza; González, Nicolle; Elgueta Sepulveda, Herman Eduardo; Hueche, Clementina; Schnettler, Berta (My University, 2021)
The object of the present reserach was to assess the psychometric properties of the Food Buying Styles Scale (Escala de Estilos de Compra de Alimentos – EEC-ALI) based on the Buying Styles Scale adapted by Denegri, Peñaloza, Elgueta and Sepúlveda (unpublished manuscript). This scale assesses planning, impulsiveness and compulsiveness with regards to food buying behavior. The sample consisted of 369 university students, male and female, from northern, central and southern Chile. We examined reliability and validity indicators. The analyses showed adequate reliability parameters for its three dimensions.Regarding its internal structure, when subjected to CFA with 18 items, the results were not satisfactory, indicating adjustment difficulties. Therefore, a new analysis was carried out with a simplified version of the instrument, eliminating some items and in order to have the optimal number of 4 items per latent variable (Kline, 2011). In the second stage, the CFA maintained the three-factor model, excluding 6 items that showed the lowest factor loadings in the previous analysis, and were the least theoretically sound. The new analysis produced more adequate levels of goodness of fit, concluding that the three-factor model with a total of 12 items can be considered adequate for its use in the analysis of food buying styles in young people and specifically university students.
Keywords: buying styles; compulsiveness; impulsiveness; planning; psychometric properties